Faktor dobra v sporte - Alexeyev, A. V. (Teorija i Praktika fiziceskoj Kul'tury, 1998)
The aim of this paper was to substantiate the opportunity of the psycho- emotional self-control in sport to create the spirit of a good in sports competitions and training studies. The author shows that each coach can master the method of autotraining to create the atmosphere of the positive emotions in training sessions and sports competitions to be kind, sympathetic and patient when working with his (her) pupils.